(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Coronavirus (Covid-19) is a large family of viruses that cause diseases ranging from mild to severe symptoms. Up to 15 Mei 2020 in Aceh there were 17 positif cases of Covid-19 with the dead 1 person and recovery of 13 people, therefore health promotion needed to increase the knowledge of blacksmith officers about Covid-19. Blacksmith workers work without using PPE, do not routinely wash their hands and there is no health promotion from local health center regarding how to prevent Covid-19. The purpose of the research is to know the effect of health promotion to the knowledge of Covid-19 on home industry workers in Pangur Village. The research method used was pre eksperimental with one group pretest – posttest without control design. The sample in this research is 25 workers blacksmith home industry with technical total sampling. The data analysis used was univariate and bivariate analysis (Dependent t Test). Univariate analysis using frequency distribution, before health promotion there is 6 (24,0%) respondents who have good knowledge about Covid-19 and after health promotion there is 21 (84%) respondents who have good knowledge about Covid-19. Bivariate analysis using t-dependent test with p-value=0,0001 (p-value ≤ α) so there is an effect of health promotion on the knowledge of Covid-19 workers blacksmith home industry in the Pangur village. Home industry owners suggested doing a health promotion program for the workers blacksmith related to increased knowledge about Covid-19 during the pandemic